Eisosome disruption by noncoding RNA deletion increases protein secretion in yeast. Issue 5 (26th October 2022) - Feng, Matthew Wenjie; Delneri, Daniela; Millar, Catherine B; O'Keefe, Raymond T
Abstract: Noncoding RNAs (ncRNAs) regulate many aspects of gene expression. We investigated how ncRNAs affected protein secretion in yeast by large-scale screening for improved endogenous invertase secretion in ncRNA deletion strains with deletion of stable unannotated transcripts (SUTs), cryptic unstable transcripts (CUTs), tRNAs, or snRNAs. We identified three candidate ncRNAs, SUT418, SUT390, and SUT125, that improved endogenous invertase secretion when deleted. As SUTs can affect expression of nearby genes, we quantified adjacent gene transcription and found that the PIL1 gene was down-regulated in the SUT125 deletion strain. Pil1 is a core component of eisosomes, nonmobile invaginations found throughout the plasma membrane. PIL1 knockout alone, or in combination with eisosome components LSP1 or SUR7, resulted in further increased secretion of invertase. Secretion of heterologous GFP was also increased upon PIL1 deletion, but this increase was signal sequence dependent. To reveal the potential for increased biopharmaceutical production, secretion of monoclonal antibody Pexelizumab scFv peptide was increased by PIL1 deletion. Global analysis of secreted proteins revealed that approximately 20% of secreted proteins, especially serine-enriched secreted proteins, including invertase, were increased upon eisosome disruption. Eisosomes are enriched with APC transporters and sphingolipids, which are essential components for secretory vesicle formation and protein sorting. Sphingolipid and serine biosynthesis pathways were up-regulated upon PIL1 deletion. We propose that increased secretion of endogenous and heterologous proteins upon PIL1 deletion resulted from sphingolipid redistribution in the plasma membrane and up-regulated sphingolipid biosynthesis. Overall, a new pathway to improve protein secretion in yeast via eisosome disruption has been identified.